Mental state, prevalence of anxiety and depression, and sociodemographic characteristics of formal and informal caregivers of hospitalized older adults - Tarosso, Beatriz Orofino; Menezes, João Daniel de Souza; da Silva, Matheus Querino; Sacardo, Yuri; dos Santos, Emerson Roberto; Ribeiro, Renato Mendonça; dos Santos, Loiane Letícia; Paschoal, Vânia Del Arco; Pompeo, Daniele Alcalá; Parro, Maria Claudia; Lima, Alba Regina de Abreu; Brienze, Vânia Maria Sabadoto; et al. (Acta Biomedica Atenei Parmensis, 2024)
Background and Aim: Population aging has increased demand for caregivers, affecting their mental health. This study aimed to characterize caregivers of hospitalized older adults, exploring sociodemographic, economic, and clinical aspects, and correlating these with their mental state, anxiety, and depression. Methods: This cross-sectional study involved 74 caregivers, assessing them with a sociodemographic questionnaire, the Hospital Anxiety and Depression Scale (HADS), and the Mini-Mental State Examination (MMSE). Statistical analyses included correlation tests and group comparisons. Results: Most caregivers were informal (89.19%), female (77.03%), Caucasian (64.86%), urban residents (93.24%), aged 50.42±14.30 years, with over eight years of education (43.24%), and working outside the home (54.05%). They had low prevalence of hypertension (68.92%), diabetes (86.49%), or other health issues (54.05%). Lower education correlated with lower MMSE scores (p=0.001); informal caregivers had lower MMSE scores than formal ones (p=0.002). Higher education related to lower HADS anxiety and depression scores (p=0.014). Conclusions: Caregivers of hospitalized older adults are mainly informal, exhibit high cognitive performance, and generally lack anxiety or depression related to their caregiving role. Education significantly influences mental health and mood symptoms, underscoring the need for tailored support and training to enhance caregivers’ well-being and quality of life.